Perceptions of training load and wellness monitoring of stellenbosch university high performance student-athletes - Starling, L.; van Velden, G.; Surmon, S.; Derman, W.; Brown, J. C. (British Journal of Sports Medicine, 2021)
Background The effective monitoring of athletes can assist in optimising their performance. This monitoring is particularly important in university student-athletes who have academic stressors additional to their training. The Stellenbosch University High Performance programme manages the top student-athletes and have implemented a training load and wellness monitoring system to assist with this.